Targeting the cyclin D/CDK4 Axis to unlock new therapeutic approaches to enhance cancer treatment - Ibrahim Khater; Aaya Nassar (PLoS ONE, 2025)
Dysregulation of the cyclin D/CDK complex is a common feature in various cancers, including colorectal, breast, and melanoma, leading to uncontrolled tumor growth and cell cycle progression. Targeting this complex has become a compelling therapeutic approach in oncology. FDA-approved CDK4/6 inhibitors, such as ribociclib, palbociclib, and abemaciclib, have demonstrated clinical efficacy, significantly improving patient outcomes. However, the development of resistance to these therapies emphasizes the urgent need for alternative strategies to overcome therapeutic limitations. The current study explores the potential of new inhibitors targeting the cyclin D/CDK axis by using virtual screening and molecular dynamics simulations. We conducted a virtual screening of the Zinc and PubChem databases, by utilizing a pharmacophore model generated by PocketQuery, to identify new candidate inhibitors of the cyclin D/CDK4 complex. The findings offer promising leads for further optimization, potentially paving the way for developing more effective treatments that circumvent resistance mechanisms and expand therapeutic options for cancer patients. Further experimental validation and in vivo studies are necessary to confirm the efficacy of these candidates and translate them into viable clinical treatments.